Hyperbaric oxygen therapy improves the effects of systemic steroid therapy for sudden sensorineural hearing loss - Yu-Ching Chen; Yu-Hsi Liu; Bor‐Hwang Kang; Cai-Sin Yao; Yao-Shen Chen; Wen-Chung Liu (Heliyon)
Objectives: This study aimed to investigate the therapeutic efficacy of combined hyperbaric oxygen therapy (HBOT) and steroid therapy in treating sudden sensorineural hearing loss (SSNHL) Design: This retrospective analysis included 505 patients diagnosed with SSNHL from August 2017 to July 2022. The patients received either a systemic steroid (SS) alone or SS with HBOT. Hearing improvement was evaluated with pure-tone audiometry (PTA). Among the participants, 102 received SS + HBOT, whereas 403 were treated with SS alone. Results: The SS + HBOT group demonstrated significantly better improvement in the PTA threshold averaged across four low frequencies (PTA4) scores (22.7 ± 23.5 vs. 16.2 ± 21.4, P = 0.007) and higher response rates (≥15 dB improvement) and significant response (≥25 dB improvement) (61.8 % vs. 44.4 %, P = 0.002; and 43.1 % vs. 22.6 %, P < 0.001, respectively) than the SS-alone group. HBOT is particularly effective in patients with hearing loss at lower frequencies. Patients treated with HBOT were 2.50 times more likely to achieve substantial hearing improvement. Patients receiving three HBOT sessions or initiating treatment within 11 days of diagnosis demonstrated optimal outcomes. Greater improvements were observed in patients with initial hearing loss of >50 dB and younger individuals. Conclusions: HBOT improves the effectiveness of SS treatment in SSNHL, with notable benefits for younger patients and those with an initial hearing loss of >50 dB. HBOT exhibited more pronounced effects at lower frequencies. Initiating HBOT within 11 days of the SSNHL diagnosis is recommended, and a regimen of five sessions is indicated for optimal results.